MOLECULAR-GENETIC APPROACHES TO IDENTIFICATION AND TYPING OF PATHOGENIC CANDIDA YEASTS - Trtkova, Jitka; Raclavsky, Vladislav (Biomedical papers, 2006)
Currently, invasive candidal infections represent an increasing cause of morbidity and mortality in seriously ill hospitalised patients. Because the accurate diagnosis of candidiasis remains difficult, a fast and reliable assay for characterization of fungal pathogens is critical for the early initiation of adequate antifungal therapy and/or for introduction of preventive measures. As novel molecular genetic techniques are continuously introduced, their role in the management of infectious diseases has also been growing. Today, molecular strategies complement conventional methods and provide more accurate and detailed insight. It can be expected that future technical development will improve their potential furthermore. In this article, we provide a critical review on the value and limitations of molecular tools in pathogenic Candida species identification and strain typing regarding their sensitivity, discriminatory power, reproducibility, cost and ease of performance.
Keywords: Candida/Infection/Typing/Molecular methods/PCR/Melting analysis